2014
DOI: 10.1177/0886260514536276
|View full text |Cite
|
Sign up to set email alerts
|

Risk Levels, Treatment Duration, and Drop Out in a Clinically Composed Outpatient Sex Offender Treatment Group

Abstract: Previous research in the Netherlands documented that clinical judgment may yield a substantial amount of treatment referrals for sexual offenders that are inconsistent with actuarial risk assessment and the Risk Need Responsivity (RNR) principles. The present study tested the risk level distribution of a high-intensity, open-format outpatient treatment group. Eighty patients were enrolled during a 620-week period, and their STATIC-99R risk levels were retrospectively determined. The distribution of risk levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…ADT is also used in male sex offenders with paraphilic or hypersexual disorder (10), either by using androgen receptor (AR) antagonists or GnRH agonists or antagonists. In contrast to prostate cancer patients, this patient group is generally younger, has less comorbidities, and is expected to need long-term treatment with ADT (11,12). However, research on adverse health effects of ADT is limited in these patients and only a few studies included data on bone health (3)(4)(5)(6)8).…”
Section: Introductionmentioning
confidence: 99%
“…ADT is also used in male sex offenders with paraphilic or hypersexual disorder (10), either by using androgen receptor (AR) antagonists or GnRH agonists or antagonists. In contrast to prostate cancer patients, this patient group is generally younger, has less comorbidities, and is expected to need long-term treatment with ADT (11,12). However, research on adverse health effects of ADT is limited in these patients and only a few studies included data on bone health (3)(4)(5)(6)8).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, use of structured risk assessment instruments is recommended but typically serves as merely one input in a larger, individualized clinical decision-making process. Recent research by Smid et al has demonstrated that these procedures can lead to treatment referrals (Smid, Kamphuis, Wever, & Van Beek, 2013) and treatment group composition (Smid, Kamphuis, Wever, & Verbruggen, in press) that are inconsistent with the RNR principles and, presumably, are associated with suboptimal outcome.…”
mentioning
confidence: 99%
“…In addition, the unnecessary prolonging of treatments should be highlighted, since shorter programs (one year or less) showed bigger effects (OR = .47; p < .001) than longer programs, which did not show a significant treatment effect (OR = .84; p > .05). Research regarding the most appropriate length of interventions is scarce, and practice varies substantially across jurisdictions (Smid, Kamphuis, Wever & Verbruggen, 2015;Yates, 2013); however, specialized literature suggests the adverse effect of long interventions may come about by the disruption of the prosocial activities and social circles (school, employment, etc.) of these individuals (Lowenkamp, Latessa, & Holsinger, 2006).…”
Section: Discussionmentioning
confidence: 99%